Robo-mate from brain muscle gathering to heavy weight lifting.
Soon, European workers with manual handling tasks could see their jobs becoming a lot more easier. Technology developed under the ROBO-MATE project is set to allow them to lift up to 15 kilograms while making it feel like it was no weight at all.